13 Patient/Carer experience of dietetic care following move to remote working during pandemic. (15th December 2021) - Renshaw, Gemma; Gardiner, Breeana
Abstract : Background/Aims: Patient reported outcome measures (PROMs) are essential in gaining valuable feedback. Due to outbreak of COVID-19, dietitians at Great Ormond Street Hospital (GOSH) were moved off site to work remotely resulting in change of practice, where patients who were previously seen face-to-face, were reviewed by telephone. The blood, cells, cancer (BCC) dietitians undertook a PROMs questionnaire to understand patient/carer experience of dietetic service and was compared to experience pre-pandemic. Methods: Parents/carers with a child under care of BCC dietitians from mid-June to September 2020 were eligible to complete online Nutrition and Dietetic Patient Outcomes Questionnaires (validated PROM tool). Children >8 years were eligible to complete young-person version of questionnaire. After review with dietitian, parents/carers were given website URL to allow optional and anonymous completion of questionnaire on own electronic devices. Responses allocated numerical values and analysed using Microsoft Excel. Results: Thirty-five parent/carers and two young persons completed questionnaire. No difference in dietetic experience observed overall (score=26.1) since pre-pandemic (score=26.1). Those who had met a dietitian once scored more favourably (score=23.7) than those who had seen dietitian twice or more (score =27.5, 26.7 respectively); in 2019, those who had seen dietitian >5 times had more positive experience (score=23.6). Reported improvement in parents/carers feeling a dietitian helped them better understand how to manage child's condition (+7%), but worse experience around managing anxiety (-9%) and increasing socialisation/interaction (-22%). Conclusions: Change to remote working during pandemic well-received by parents/carers under BCC dietitians at GOSH. Data collected during national lockdown likely impacted results around anxiety and socialisation; however, impact of face-to-face reviews in reducing anxiety must be considered. A combination of face-to-face reviews and remote working is likely to become new model of care. Repeat questionnaire is needed once new ways of working implemented. Methods of gathering data from young children needs further consideration.